Therapy guidance by vaginal smears of pregnant women with preterm complications in correlation with maternal and neonatal outcome: a retrospective analysis - Stefanovic, Stefan; Werner, Eva; Gerigk, Marlis; Hornung, Ralph; Karic, Uros; Weiß, Christel; Tuschy, Benjamin; Berlit, Sebastian; Sütterlin, Marc (In vivo, 2023)
Background/Aim: This retrospective cohort study enrolled hospitalized women with 24+0 to 33+6 gestational weeks with conditions associated with preterm birth. We evaluated the ability of vaginal swab isolates to guide antibiotic management decisions in the setting of threatened preterm towards a clinical advantage, i.e., longer delay between diagnosis and birth, better neonatal outcomes. Patients and Methods: Vaginal swabs were obtained from all patients and antibiotic resistance profiles determined in case of growth. The cohort was divided into two groups: the antibiogram-noncongruently managed Group 1 and the antibiogram-congruently managed Group 2. These groups were compared in regard to multiple maternal and neonatal endpoints. Results: In total, 698 cases were analyzed - 224 in Group 1 and 474 in Group 2. Antibiotics were ordered/continued by the treating physician in 138 cases (138/698; 19.8%) upon review of vaginal swab cultures results. Forty-five among them (32.6%) received antibiotics inactive against the isolated bacteria. 335 (25.4%) patients had only normal vaginal flora, and 95.6% of them had not received antibiotics. Facultatively pathogenic microorganisms were isolated in 52% patients. Only 5% of the neonates had bacterial isolates identical to those of their mothers. There were no significant differences in outcomes between Group 1 and Group 2. Conclusion: No association was found between a swab-result-guided antibiotic management protocol and maternal or fetal outcome in the setting of preterm birth risk between 24 and 34 gestational weeks. These findings underline the importance of critical rethinking the frequency of vaginal smears and fine-tuning the indications for antibiotic treatment.